Trends in Dry Pea (Pisum sativum L.) Production - Lazányi, János (Acta Agraria Debreceniensis, 2002)
Dry pea is an important, cool-season grain legume, which is grown worldwide on over 6 million hectares. The major producing countries outside Europe are China and Canada, followed by India, Australia, and the United States. France, Canada and Australia produce over 2 million hectares and are major exporters of peas. During the 1980’s, in developed countries of the European Union, pea production rose yearly by 6-10%, which represents a significant increase in both area and yield. Europe accounts for 50-75% of world pea production. In the 1990’s, the European Union produced 4-5 million tonnes of dry pea, of which 3-4 million tonnes were used for feed and 1 million tonnes for export. At the end of the 20th century, the growth in production was low, mainly because of the absence of support measures, and the better returns offered by other crops. In the countries of the former Soviet Union, dry pea was primarily used as feed and pea production dropped, due to a trend in livestock raising.Food consumption of dry pea is concentrated in developing countries, where grain legumes represent a useful complement to cereal-based diets as a relatively inexpensive source of high quality protein. As a result, human consumption of grain legumes fell from 2,2 kg/capita in 1961 to 0,5 kg/capita in 1999. The importance of grain legumes in food protein supply decreased, while that of cereal products increased. Shortage of grain legumes has adverse effects on the nutritional standard of poor people in developing countries.World dry pea production reached 16,7 million tonnes in 1990, with 3,7 million tonnes used as food, 11,4 million tonnes used as feed, and 1,0 million tonnes used as seed. Dry pea production was 10,9 million tonnes in 1999, and 3,5, 5,8 and 0,8 million tonnes was used as food, feed and seed, respectively. In the coming decades, world grain legume production and utilization as feed are expected to expand at a slower rate than in the 1980’s. Most of the increase is expected to occur in Eastern European countries, Canada and Australia, where production is anticipated to grow at 2% annually. The projection for the new millennium was derived from adjusted trends in area and yield over the period 1961-2000, based on FAO statistical data.